Immunohistochemistry analyses of the abomasal mucosa show differences in cellular-mediated immune responses to Haemonchus contortus infection in resistant and susceptible young lambs - Lins, José Gabriel Gonçalves [UNESP]; Albuquerque, Ana Cláudia A. [UNESP]; Louvandini, Helder; Amarante, Alessandro F.T. [UNESP] (Elsevier, 2024)
Haemonchus contortus is known for its high pathogenicity in sheep, and the uncontrolled use of anthelmintics resulted in the emergence of multiple drug-resistant populations. Breeding sheep for gastrointestinal nematode resistance is a sustainable alternative to reduce dependence of anthelmintic drugs, and differences in the degree of resistance between breeds have been reported. Here we compare two sheep breeds (Santa Ines and Ile de France), concerning the differences in innate and adaptive immune response involved in the resistance against H. contortus infection. Immunohistochemical analyses of the abomasum were conducted in naïve Santa Ines (n = 14) and Ile de France (n = 12) lambs randomized into four groups: infected Santa Ines (n = 8), non-infected control Santa Ines (n = 6), infected Ile de France (n = 8), and non-infected control Ile de France (n = 4). The infected lambs were initially infected with H. contortus infective larvae at 14 days of age, and multiple infections were conducted every second day until they reached 66 days of age. There was a significant effect (P < 0.001) of the infection with increase in numbers of CD3+ T; CD79α+ B; GATA3+ Th2/ILC2; POU2F3+ tuft cells; FOXP3+ T reg; and IgE + cells in the fundus of the abomasal mucosa in both Santa Ines and Ile de France lambs. Nevertheless, the infected Santa Ines lambs presented the highest averages for CD79α+ B; GATA3+ Th2/ILC; IgE + cells; and POU2F3+ tuft cells and there was a significant association of the breed and infection status with regards to POU2F3+ tuft cells, with the highest mean in the infected Santa Ines group. The infected Santa Ines group had three lambs with high degree of resistance and five lambs that showed a moderate infection. Our results suggest a mechanism of synergistic coordination between different immune-cell types in promoting resistance of suckling lambs under H. contortus infection.
Keywords: Adaptive immunity; Breeding for resistance; Innate immunity; Sustainable nematode control; Th2 response